Evaluating the Efficacy of the EJOY English Application to Escalate Eleventh-Grade Students’ Speaking Proficiency - Winda Ocvi Saskiana; Dian Fadhilawati; Miza Rahmatika Aini (Universitas Islam Balitar, 2024)
This study assessed the EJOY application’s efficacy in enhancing eleventh-grade students' oral proficiency in explaining natural phenomena, focusing on pronunciation, vocabulary, fluency, grammar, and content. Pre-experimental research utilizing a one-group pretest and post-test design covered thirty-five students at SMAN 1 Blitar, especially class XI-MIPA3. The study unfolded in three phases: pretest, treatment, and post-test, with a preliminary tryout to ensure test validity and reliability. Data analysis, conducted using a paired sampled T-test with SPSS 26, revealed a significant improvement in students' speaking achievement in explanation texts. Rising from 72.00 to 80.62. In addition, the Sig 2 tailed was under 0.05. It was stated that the Ejoy application effectively improves students’ speaking skills. From the findings, students should use the EJOY application in English to refine their speaking skills. Further, English educators are advised to integrate the EJOY Application to enhance learning outcomes or incorporate it into other topics to create more engaging and interactive curricula tailored to specific learning objectives.